2021
DOI: 10.1186/s12889-021-10484-7
|View full text |Cite
|
Sign up to set email alerts
|

Screen time duration and timing: effects on obesity, physical activity, dry eyes, and learning ability in elementary school children

Abstract: Background As internet use becomes more widespread, the screen time (ST) of elementary school students increases yearly. It is known that longer durations of ST can affect obesity, physical activity, dry eye disease, and learning ability. However, the effects of ST just before bedtime have not been clarified. Therefore, we examined ST duration and timing effects on elementary school children. Methods We conducted a survey of 7419 elementary school … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
2
43
0
5
Order By: Relevance
“…For instance, there is a clear association between children's television viewing of more than 2 h per day and lower well-being, less self-control and emotional stability (Twenge and Campbell, 2018), decreased fitness (Hardy et al, 2018), lower school and academic performance (Howie et al, 2020;Mineshita et al, 2021), reduced social skills (Hinkley et al, 2010), cardio-vascular diseases (Lissak, 2018) as well as mental and social disorders (Pagani et al, 2016;Stiglic and Viner, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there is a clear association between children's television viewing of more than 2 h per day and lower well-being, less self-control and emotional stability (Twenge and Campbell, 2018), decreased fitness (Hardy et al, 2018), lower school and academic performance (Howie et al, 2020;Mineshita et al, 2021), reduced social skills (Hinkley et al, 2010), cardio-vascular diseases (Lissak, 2018) as well as mental and social disorders (Pagani et al, 2016;Stiglic and Viner, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Уже к 2010 г. рекомендованные ВОЗ лимиты были превышены в Японии (к 18 мес 86% детей проводили перед телевизором более 1 ч/сут) [27] Другая картина наблюдается в связи со школьной (академической) успеваемостью. Множество исследований в разных странах (США [31], Канада [32], Великобритания [33], Нидерланды [34,35], Испания [36,37], Австралия [38], Япония [39,40], Южная Корея [41], Китай [42]) демонстрируют связь более длительного экранного времени и использования электронных гаджетов детьми с их низкой успеваемостью. При этом в указанных источниках это установлено в отношении общего экранного времени, а также для использования мобильных телефонов / смартфонов [33,36] и социальных сетей [34,35].…”
Section: экранное время и познавательное развитие в раннем детствеunclassified
“…The long-term effects of this increase in electronic device use on physical and mental health are unknown and will take years to determine. Before COVID-19, the negative effect of prolonged screen time on the health of the ocular surface was known 1 and the increased use of electronic devices necessitated by the pandemic will exacerbate this problem. 2 In addition, once the current health crisis subsides, many people will continue to work, learn, and socialize remotely through electronic devices so that the effect of screen time on the ocular health will continue to be an issue for the foreseeable future.…”
mentioning
confidence: 99%
“… 3 This is also true for patients of almost all ages; before COVID-19, in 2018, Sheppard and Wolffsohn 4 reported that 68% of children regularly use a computer by age 3 and 37% of adults aged 60 years and older spend 5 or more hours daily on digital devices. Mineshita et al's 1 recent study of 7,419 elementary school children in Japan found that, in addition to dry eye, increased screen time is associated with obesity, decreased physical activity, and reduced academic performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation